The Effect of Interfacial Tension and Thermal Stability on Surfactant Injection - Aqlyna Fattahanisa; Rini Setiati; Sugiatmo Kasmungin (Penerbitan Universitas Trisakti, 2018)
In this research, bagasse NaLS surfactant was used as an injecting reservoir fluid at low salinity. The purpose of this study was to observe the effect of IFT and thermal stability on oil recovery factors in various compositions. The material used in this study isbagasse based NaLS surfactant, light oil and sandstone, while spinning drop is used to measure the interface tension. The oven was used for thermal stability testing and core flooding equipment for the surfactant injection. The success in this study was based on the value of the recovery factor, the small IFT value, and stability of IFT in the thermal stability test. The IFT results obtained for CF1, CF5,and CF7 were 10.4 mN / m, 4.09 mN / m, and 4.34 mN / m, respectively. Based on The results of the thermal stability test only the CF7 was stable with an IFT value of 2.11 mN / m, while the other two variations were unstable. The recover factor of CF1, CF5, and CF7 was 3.24%, 3.52%, and 5.34%, respectively. It can be concluded that IFT as well as thermal stability affect the frecovery factor.